Volume 2: Theory and Fundamental Research; Aerospace Heat Transfer; Gas Turbine Heat Transfer; Computational Heat Transfer 2009
DOI: 10.1115/ht2009-88303
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Evaluation of 2D and 3D Steady and Unsteady Flows of a Pair of Opposing Confined Impinging Air Jets

Abstract: The steady and unsteady laminar flow and heat transfer characteristics for a pair of opposing confined impinging slot jets in 2D and 3D were evaluated numerically at two Reynolds numbers. The present study continues the authors’ earlier work [1] and identifies the main similarities and differences arising from the expansion to the third dimension. At lower Reynolds number jet (Re = 300), the flow interaction produces a symmetric, steady flow hydrodynamic pattern with the jets being deflected laterally for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…This motion causes the stagnation point locations to sweep back and forth. The sweeping motion increases the cooling effective area, thus leading to enhanced heat transfer coefficients, opposed to previous studies [20] when the stagnation "bubble" developing on the target wall between the two jets caused a large reduction in the effective heat transfer removal from the two heat flux sources. Hence, the impact of a stagnation region on heat transfer is highly dependent on the relative location and distance between the two heat sources placed on the channel walls.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…This motion causes the stagnation point locations to sweep back and forth. The sweeping motion increases the cooling effective area, thus leading to enhanced heat transfer coefficients, opposed to previous studies [20] when the stagnation "bubble" developing on the target wall between the two jets caused a large reduction in the effective heat transfer removal from the two heat flux sources. Hence, the impact of a stagnation region on heat transfer is highly dependent on the relative location and distance between the two heat sources placed on the channel walls.…”
Section: Resultscontrasting
confidence: 53%
“…A previous study [20] indicated that the 3D opposite jets at lower Re = 300 become slightly unsteady compared to the steady 2D jets at same Re number.…”
Section: Resultsmentioning
confidence: 95%